2012
DOI: 10.1090/s0002-9939-2012-11274-2
|View full text |Cite
|
Sign up to set email alerts
|

A note on the Turán function of even cycles

Abstract: Abstract. The Turán function ex(n, F ) is the maximum number of edges in an F -free graph on n vertices. The question of estimating this function for F = C 2k , the cycle of length 2k, is one of the central open questions in this area that goes back to the 1930s. We prove that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 17 publications
0
50
0
Order By: Relevance
“…Bondy and Simonovits [3] (and independently Erdős) showed that ex(n, C 2k ) = O(n 1+1/k ). Subsequent improvements on the leading coefficient were found by Verstraëte [23] and more recently by Pikhurko [20].…”
Section: Introductionmentioning
confidence: 90%
“…Bondy and Simonovits [3] (and independently Erdős) showed that ex(n, C 2k ) = O(n 1+1/k ). Subsequent improvements on the leading coefficient were found by Verstraëte [23] and more recently by Pikhurko [20].…”
Section: Introductionmentioning
confidence: 90%
“…We start by mentioning the Turán numbers of even cycles in the graph case. A classic theorem of Bondy and Simonovits [4] shows that ex(n, C 2k ) ≤ 100k · n 1+1/k , and this bound was improved by several authors in [36,30,6]. The current best known upper bound is the following one obtained by Bukh and Jiang [6] ex(n, C 2k ) ≤ 80 k log k · n 1+1/k + O(n).…”
Section: Turán Numbers Of Berge Cycles In R-graphsmentioning
confidence: 99%
“…A classic theorem of Bondy and Simonovits [4] shows that ex(n, C 2k ) ≤ 100k · n 1+1/k . This bound was subsequently improved by several authors in [36,30,6]. The Turán problem for cycles in hypergraphs has been investigated for different notions of hypergraph cycles in [3,17,18,20,21,25] among others.…”
mentioning
confidence: 99%
“…In particular, for graphs (i.e., 2-uniform hypergraphs) the C 2 -free condition does not impose any restriction, and there is no difference between a (Berge) cycle C l and a linear cycle C lin l . Bondy and Simonovits [5] showed that for k ≥ 2, ex(n, C 2k ) ≤ c k n 1+ 1 k for all sufficiently large n. Improvements to the constant factor c k are made in [22,18,7]. The girth of a graph is the length of a shortest cycle contained in the graph.…”
Section: Introductionmentioning
confidence: 99%